Coagulopathy in COVID-19 and Its Implication for Safe and Efficacious Thromboprophylaxis - Langer, Florian; Kluge, Stefan; Klamroth, Robert; Oldenburg, Johannes (Hämostaseologie, 2020)
The novel coronavirus, SARS-CoV-2, is causing a global pandemic of life-threatening multiorgan disease, called COVID-19. Accumulating evidence indicates that patients with COVID-19 are at significant risk of thromboembolic complications, mainly affecting the venous, but also the arterial vascular system. While the risk of venous thromboembolism (VTE) appears to be higher in patients requiring intensive care unit support compared to those admitted to general wards, recent autopsy findings and data on the timing of VTE diagnosis relative to hospitalization clearly suggest that thromboembolic events also contribute to morbidity and mortality in the ambulatory setting. In addition to a severe hypercoagulable state caused by systemic inflammation and viral endotheliitis, some patients with advanced COVID-19 may develop a coagulopathy, which meets established laboratory criteria for disseminated intravascular coagulation, but is not typically associated with relevant bleeding. Similar to other medical societies, the Society of Thrombosis and Haemostasis Research has issued empirical recommendations on initiation, dosing, and duration of pharmacological VTE prophylaxis in COVID-19 patients.
Keywords: COVID-19; deep vein thrombosis; pulmonary embolism; coagulopathy